Anti-soviet behavior - Klumbys, Valdemaras (Genocidas ir rezistencija, 2010)
The article discusses one of the models of behaviour typical to Lithuanian society in the Soviet period, namely anti-Soviet behaviour, which was particularly characteristic to the cultural elite of the time. It is described as the activity of opposing the Soviet regime, but not exceeding the permissible limits of activities and thus not being repressed by the regime. The article states that such behaviour supplemented the conformance of society (when resistance is understood as the antipode to conformance). In the author’s opinion, the opposition may be treated as the result of the interplay between the pressure of the regime and the values opposing to the regime, a certain compromise between the pressure of the regime on the one hand and the pressure of the values opposing the regime on the other hand.The article distinguishes three levels of anti-Soviet behaviour. Social opposition is defined as resistance to the regime on a daily social level, ignoring the norms of behaviour proclaimed by the regime. The author maintains that such non-political activity that did not do direct harm to the regime increased alienation of people with the Soviet regime and weakened both the impact of the regime on society and the regime itself.Institutional opposition, which is given major focus in the article, is defined as activities, particularly cultural activities, of the nation and for the sake of Lithuania dedicated to the preservation and support of national identity, culture, and the nation. It also includes public criticism of Soviet maladies and individual characteristics of the regime, artistic semi-nonconformism, the use of anti-Soviet overtones in creative work, and other manifestations of disagreement with the ideology of the regime. The author maintains that this institutional opposition manifested itself in the activities carried out at official institutions and in the public space controlled by the regime. It is also asserted that official public national manifestations during the post-Stalin period, part of which were the result of opposition activity, cannot be considered useful only to the regime. Publicity allowed for the opposition to spread widely and most efficiently nurture Lithuanian identity, even though ridden with ideology. In the author’s opinion, the opposition fit into the frame of the Soviet ‘social contract’ (people had to perform the mandatory rituals and not agitate publicly against Soviet power, whereas the regime leniently viewed the actual beliefs of people). The article discusses the crossing of the limit of permissibility as the criterion for allocating the activity to anti-Soviet activity and states that crossing such a threshold is difficult for researchers to identify. It is also affirmed that the regime sought to use the activities of institutional opposition for its own sake. It can therefore be stated that the opposition’s stance was at least partially useful to the regime.Semi-legal activity is singled out as the highest level of opposition. It is defined as active participation in organisations that are formally Soviet but only slightly controlled by the regime or in loosely organised movements, usually of a national nature. The relationship of this activity with the opposition is defined.
Keywords: Soviet regime; society; resistance